Can Infection by Sars-Cov2 Induce Systemic Lupus Erythematosus Reactivation? - García, Carlos (2023)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune chronic multi-organic diseasecharacterized by a deregulated innate and adaptive response. A series of viral and bacterial agentshave been associated with SLE activation. Coronavirus family represents important infectiouspathogens in both humans and animals, being responsible for approximately one third of community acquired superior respiratory tract infections. At the end of 2019, a new coronavirus (SARS-CoV-2) was detected as responsible for the COVID-19 disease. It was decided to evaluate if SLE patients had a greater risk of lupus activation when contracting COVID-19.Material & Method: Sixty two COVID-19 infected SLE patients were studied, comparing thosewho had suffered lupus reactivation versus those who had not. Renal function, autoinmunity andinflammation markers, and SLE reactivation risk was compared between both groups.Result: COVID-19 infection in SLE patients did not elevate lupus reactivation risk: OR: 0.8 (0.3-2.6), p: 0.7.Conclusion: COVID-19 is not, at the moment and as documented, a risk factor for SLE reactivation.